Unilateral forgiveness : forgiveness in the absence of apology (2018)
According to conditional theories, forgiveness is unreasonable unless the wrongdoer complies with conditions that make them worthy of it (Griswold, 2007; Murphy, 1988; Swinburne, 1989). These conditions are meant to ensure respect for the victim and proper condemnation of the offense. The wrongdoer, we are told, ought to repent, apologize, atone, repair, and so forth. There are, however, cases that do not fit this paradigm. Sometimes victims have good reasons to unilaterally forgive someone who has not complied with conditions that would otherwise make them deserving of forgiveness. In this paper, I argue that unilateral forgiveness need not be, as conditional theories would have it, a moral mistake. In fact, in some cases unilateral forgiveness constitutes a reasonable response to a wrongdoing. These are scenarios in which the standard considerations to resent others, to feel indignation for what they did, and to sever our relationships with them hold.